The Great Mosque of Bangkalan Through Time: Inscriptions, Architecture, and Function of the Mosque - Zulaili, Iin Nur; Zanki, Nurudin; Hotimah, Husnul (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This research aims to study the Grand Mosque of Bangkalan as one of the cultural and social heritage that has historical, inscriptions and architectural value on the building, as well as important functions for the community of Bangkalan, Madura.The study focuses on three main aspects: the history of the mosque, the artistic characteristics of the architecture of the mosque, and the function and role of the mosque from its inception to the present. This research uses a historical-qualitative approach with library study and field observation methods. Research sources use primary sources in the form of carvings of inscriptions and secondary sources in the form of websites, journals, and books relevant to this research topic. The results of the study show that the Great Mosque of Bangkalan is not only a center for religious activities, but also a symbol of the cultural identity of the Madurese people. In terms of architecture, this mosque reflects a blend of local architectural styles, Javanese, and distinctive colonial influences, making it unique and rich in aesthetic value. In addition, the function of the mosque has undergone a dynamic transformation, not only as a place of worship, but also as a center for education, social, and community activities. These findings indicate that the Great Mosque of Bangkalan has an important value as a historical heritage that continues to live and is relevant in people's lives to this day.